Common sense and nuclear warfare - Russell, Bertrand (London, 2010)
Written at the height of the Cold War in 1959, Common Sense and Nuclear Warfare was published in an effort 'to prevent the catastrophe which would result from a large scale H-bomb war'. Bertrand Russell's staunch anti-war stance is made very clear in this highly controversial text, which outlines his sharp insights into the threat of nuclear conflict and what should be done to avoid it. Russell's argument, that the only way to end the threat of nuclear war is to end war itself, is as relevant today as it was on first publication.
Keywords: Nuclear Warfare